Pedampingan Keluarga Anak Stunting Dan Wasting Lokus Stunting Dan Wasting Kelurahan Ulujami Kecamatan Pesanggrahan Kota Jakarta Selatan - Sugeng Wiyono; Mochamad Rachmat; Syarifah Miftahul El Jannah; Debby Ariesta; Agita Eka Kusumastuti; Rifda Nurjannah; Rose Angelina Suwandi; Ratna Suci Amalia; Rana Salsabila Heriana; Syahrul Sani; Iqbal Bagas Febriansyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
President Joko Widodo in 2085 dreams of Indonesia's human resources having superior intelligence compared to other countries. In the medical field, life expectancy has increased, quality of life has improved and the health system has become better. The 2022 Indonesian Nutrition Status Survey shows that 7.7% of children under five are thin, 17.1% underweight, 3.5% overweight and 21.6% short. The prevalence of stunted children under five in Indonesia is number 4 globally and 2 in Southeast Asia. The prevalence of stunted toddlers at the national level is equivalent to 6 million Indonesian children with the potential to lose an Intelligence Quotient (IQ) of 10 to 15, and to improve nutrition for stunted children it is estimated that it will require 300-400 trillion. Research by Tassew Woldehanna, et al in 2018 in Ethiopia explained that children who experienced stunting had scored 16.1% lower on vocabulary tests and 48.8% lower on quantitative assessment tests. The general objective is to improve the status of the target family subject to assistance. While the specific objectives include: a). Increasing mothers' knowledge of the subject of the target family for assistance b). Improving the nutritional status of children under five with stunting, wasting, and obesity, c. Improving clean and healthy living behavior in target families for assistance The families of the mentoring participants consisted of fathers aged ≥30 years, 71.4%, all with high school education, 28.6% were self-employed. Meanwhile, 28.6% of mothers aged <30 years were housewives and 85.7% had graduated from high school. After mentoring, there was a significant increase in nutrition and health knowledge (p=0.032) of 25.9 points. There were significant changes in knowledge and actions before and after mentoring However, there was no increase in the child's weight after the assistance was provided.